Analisis Penggunaan Media Audiobook Cerita Rakyat Kalimantan Timur Terhadap Keterampilan Menyimak Siswa Sekolah Dasar - Siska Oktaviani; Ratna Khairunnisa (Shofanah Media Berkah, 2025)
Listening skills are a fundamental competence that students need to master, particularly at the elementary school level. However, listening activities are still often perceived as less engaging and tend to be monotonous. The development of educational technology, including audiobook media, offers opportunities to support the improvement of students’ listening skills. This study aims to analyze the use of East Kalimantan folklore audiobooks among elementary school students as an alternative learning medium that is expected to address students’ low interest and boredom in listening activities, thereby enabling more effective listening. This research employed a qualitative descriptive approach with fourth-grade students of SDN 004 Samarinda Utara as the research subjects. Data collection techniques included listening comprehension tests consisting of four aspects—memory, comprehension, application, and analysis—as well as interviews and documentation. The findings indicate that students still experience difficulties in recalling important information from the stories. In addition, students are not accustomed to engaging in structured listening activities. Based on these findings, it can be concluded that the implementation of listening activities using audiobook media has not yet fully reduced students’ boredom, resulting in suboptimal understanding of the content, meaning, and messages conveyed in the stories.